The New Diplomacy: Devising a Relational Model of Public Diplomacy - Anne E Buckle (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
Public diplomacy, an open form of international politics, is essential for building state relations and improving the American image in current times, particularly in light of the recent leakage of some 250,000 classified State Department cables. The ways embassy officials conduct diplomacy must be more candid if they are to gain trust from local populations. Contemporary technology and new media have drastically modified the ways states conduct foreign policy, and embassies must cater to this environment by reaching out to mass publics using novel approaches. Additionally, a new kind of public diplomacy is emerging, one involving private sector networks. In a series of two case studies, the first investigating the role of the Public Affairs section of the U.S. Embassy in Paris, France, and the second looking at an international visitor event at the University of Tennessee, Knoxville, I observed two different kinds of public diplomacy in action and quickly discovered the power of cultural education initiatives and interpersonal relationship-building efforts in developing and sustaining international political relations.
Keywords: Diplomacy; Political Science; Public Affairs; Politics